2022
DOI: 10.1186/s13049-022-01027-z
|View full text |Cite
|
Sign up to set email alerts
|

Initial experiences of prehospital blood product transfusions between 2016 and 2020 in Päijät-Häme hospital district, Finland

Abstract: Background Treating hemorrhaging patients with prehospital blood product transfusions (PHBT) narrows transfusion delays and potentially benefits the patient. We describe our initial experiences of PHBT in a ground-based emergency medical service (EMS), where the transfusion protocol covers both traumatic and nontraumatic hemorrhaging patients. Methods A descriptive retrospective analysis was performed on the records of all the patients receiving re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Recent PrehoPLYO 24 and RePHILL 37 trials did not show survival improvement when using PHT in trauma patients. However, medical pathologies are the first causes of PHT according to our results, which is confirmed by the few European practice studies available 38,39 . Data are poor for these PHT indications.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recent PrehoPLYO 24 and RePHILL 37 trials did not show survival improvement when using PHT in trauma patients. However, medical pathologies are the first causes of PHT according to our results, which is confirmed by the few European practice studies available 38,39 . Data are poor for these PHT indications.…”
Section: Discussionsupporting
confidence: 80%
“…However, medical pathologies are the first causes of PHT according to our results, which is confirmed by the few European practice studies available. 38,39 Data are poor for these PHT indications.…”
Section: Discussionmentioning
confidence: 99%
“…In Finnish studies of prehospital blood product recipients, the short-term mortality rate has been reported to be 18%-33%. [33][34][35] Taken together, we are likely to overestimate the potential for RhD alloimmunization and the true alloimmunization rate would probably be lower than the calculated one.…”
Section: Discussionmentioning
confidence: 74%
“…18 Recent data from our rural emergency medical service (EMS) area showed that PHBT was started a median of 61 min before admission. 19 We have estimated that 100-125 patients per year are transfused with blood products during prehospital care in Finland. 20 Of them, 23%-44% are also nontrauma patients (e.g., gastrointestinal bleeding, obstetric, or vascular emergencies).…”
Section: Introductionmentioning
confidence: 99%
“…20 Of them, 23%-44% are also nontrauma patients (e.g., gastrointestinal bleeding, obstetric, or vascular emergencies). 18,19,21 In this study, we retrospectively analyzed all adult (age ≥16 years) blunt trauma patients with new injury severity score (NISS) >15 treated by a P-S PHEC unit from the Helsinki Trauma Registry (HTR) with PHBT capability between Mach 2016 and July 2021. Our aim was to identify factors affecting the decision to start PHBT at the site of an accident.…”
Section: Introductionmentioning
confidence: 99%